2005
DOI: 10.1104/pp.105.065607
|View full text |Cite
|
Sign up to set email alerts
|

Cell-to-Cell Movement of Green Fluorescent Protein Reveals Post-Phloem Transport in the Outer Integument and Identifies Symplastic Domains in Arabidopsis Seeds and Embryos

Abstract: Developing Arabidopsis (Arabidopsis thaliana) seeds and embryos represent a complex set of cell layers and tissues that mediate the transport and partitioning of carbohydrates, amino acids, hormones, and signaling molecules from the terminal end of the funicular phloem to and between these seed tissues and eventually to the growing embryo. This article provides a detailed analysis of the symplastic domains and the cell-to-cell connectivity from the end of the funiculus to the embryo, and within the embryo duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
294
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(309 citation statements)
references
References 72 publications
(88 reference statements)
11
294
0
4
Order By: Relevance
“…Being much larger than 3ϫGFP whose cell-to-cell movement was very limited, GNOM should be restricted to the cells of expression. This is also supported by the specificity of observed rescue phenotypes of different transactivation lines: although suspensor and globular embryo form a symplastic continuum for 1ϫGFP (27 kDa) (Stadler et al, 2005), GNOM transactivation from the suspensor and hypophyseal promoters showed distinct phenotypes. Detection of low-level protein expression is always problematic.…”
Section: Gnom-induced Auxin Drainagesupporting
confidence: 51%
“…Being much larger than 3ϫGFP whose cell-to-cell movement was very limited, GNOM should be restricted to the cells of expression. This is also supported by the specificity of observed rescue phenotypes of different transactivation lines: although suspensor and globular embryo form a symplastic continuum for 1ϫGFP (27 kDa) (Stadler et al, 2005), GNOM transactivation from the suspensor and hypophyseal promoters showed distinct phenotypes. Detection of low-level protein expression is always problematic.…”
Section: Gnom-induced Auxin Drainagesupporting
confidence: 51%
“…Developing Arabidopsis seeds have at least three apoplasmic borders that require membrane transporters: (1) between the outer integument (a symplasmic extension of the phloem) and the inner integument; (2) between the inner integument and the endosperm; and (3) between the endosperm and the embryo (Stadler et al, 2005). Based on expression patterns, all three SWEETs contribute in cascade-like patterns to distinct steps in seed filling.…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis thaliana, sugars are delivered to the maternal seed coat via the funicular phloem, which is symplasmically connected to the outer integument (Stadler et al, 2005). Sugars are released from the outer integument to the inner integument, and potentially the suspensor, followed by secretion into the seed apoplasm by yet unknown membrane transport mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this hypothesis, we detected starch granules in the nucellus. Nevertheless, nutrients were shown to travel to the endosperm and embryo via the seed coat (Stadler et al, 2005;Chen et al, 2015). Further analyses are necessary to determine whether nutrients are allocated to the endosperm also through the nucellus.…”
Section: Developmental Progression Of Nucellus Degenerationmentioning
confidence: 99%